EFFORTS TO IMPROVE STUDENT LEARNING ACHIEVEMENT USING HUMANISTIC LEARNING THEORY - Hasan Basri; Sukardi Sukardi (Educare : Jurnal Ilmu Pendidikan, 2022)
This study discusses the application of humanistic theory in improving student achievement at MI Nurul Yakin Sumberanyar Paiton. This research uses qualitative research method of case study type. This research was conducted since April 30, 2022. The data sources are observations and interviews. To obtain valid and reliable data, the researcher conducted interviews with several informants using purposive sampling technique, which consisted of five people, namely Ning Durrotus Shaimah as the principal, Hani as the deputy head, Titin as the deputy head of the curriculum, Cici Malika as one of the teachers, and Afkara Raysifa one of the students at the institution. The data analysis is data collection, data reduction, data display, and conclusions. The research results obtained are (1) the existence of adequate facilities and infrastructure, (2) the provision of rewards, (3) the existence of professional teachers and (4) student-centered learning strategies. With the application of humanist learning theory, it is possible for student achievement to be achieved.